Research subject one of 2 bears shot: FINAL Edition (The Vancouver sun (1986), 1993)
All black-bear hunters must have a hunting licence and a black-bear tag for the current hunting season, which opened last weekend, said Dan Dwyer. Dwyer said Magic had provided excellent data, some of it during hibernation in a stump of second-growth forest in the Nimpkish Valley area about 340 kilometres north of Victoria. Dwyer said he thought poachers might have brought down the bears but no body parts were removed.